Stability Analysis of Runge-Kutta Methods for Nonlinear Systems of Pantograph Equations (Journal of Computational Mathematics, 2005)
This paper is concerned with numerical stability of nonlinear systems of pantograph equations. Numerical methods based on $(k,l)-$algebraically stable Runge-Kutta methods are suggested. Global and asymptotic stability conditions for the presented methods are derived.
Keywords: Nonlinear pantograph equations; Runge-Kutta methods; Numerical stability; Asymptotic stability.